HUBUNGAN PENGETAHUAN, SIKAP, DAN PENDIDIKAN REMAJA DENGAN KEJADIAN PERNIKAHAN USIA DINI DI DESA ULAK PATIAN KECAMATAN KEPENUHAN KABUPATEN ROKAN HULU TAHUN 2023 - Eka Yuli Handayani; Fitri Yanti; Siti Nurkhasanah; Sri Wulandari (Maternity and Neonatal : Jurnal Kebidanan, 2023)
The Background of early marriage is a marriage that is carried out it a young age between two young couples who have not reaached the age limit. Whose eventual impact on the well-being of families and in society as a whole. The aim of the study was to determine the relationship between knowledge, attitudes, and youth education with the incidence of earli marriage in the village of Ulak Patian Kepenuhan sub-districtRokan Hulu district. The research method is quantitative analytic with a cross sectional approach. The results of research 95 respondents who did early marriage were 89 (93.7%) respondents, while those who did not were 6 (6,3%) respondents. Respondents with less knowledge were 64 (67.4%) and respondents with good knowledge were 31 (32.6%) respondents. Respondents with a negative attitude 44 (46.3%) respondents and a positive attitude as many as 51 (53.7%) respondents. Respondents with low educatin were 82 (86.3%) and with high education were 13 (13,7%). There is a relationship between knoweledge and early marriagr (0,000), There is not a relationship between attitude and early marriagr (1,000), There is a relationship between education and early marriagr (0,039). Conclusion, there is a relationship between knoweledge and early marriagr, there is not a relationship between attitude and early marriage. There is a relationship between education and early marriage. Suggestions are ecpected as input for adolescents and forms of prevention of marriage at an early age so as not to engage in early marriage.